A snapshot of gay-straight alliance clubs and student well-being in Western Canadian high schools - Di Stasio, Maria; Alston, Lauren; Harley, Jason (My University, 2023)
Gay-Straight Alliance (GSA) clubs promote safer school environments for students. GSAs typically refer to student-led, teacher-supported school clubs that serve youth of diverse gender identities and sexual orientations. This study investigated the relationship between students’ awareness of school-based GSAs and their bullying experiences, mental health, self-determination, and relationships at school and home. Findings showed that LGBTQ2S+ students experienced higher rates of bullying and symptoms of depression and scored lower on self-determination subscales than cisgender heterosexual students. Interestingly, students who were aware of their school’s GSA club scored higher on the self-determination subscales regarding family relationships and lower on bullying compared to students who were unaware of their school’s GSA club. LGBTQ2S+ students had lower rates of comfort with their sexual orientation at home and school than their cisgender heterosexual students. Implications and future directions are discussed.
Keywords: gay-straight alliance; high school; self-determination; bullying; depression